2011
DOI: 10.3390/ijms12052901
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Roles of the Four Conserved Acidic Residues in the Thermal Stability of Poly(A)-Specific Ribonuclease

Abstract: Divalent metal ions are essential for the efficient catalysis and structural stability of many nucleotidyl-transfer enzymes. Poly(A)-specific ribonuclease (PARN) belongs to the DEDD superfamily of 3′-exonucleases, and the active site of PARN contains four conserved acidic amino acid residues that coordinate two Mg2+ ions. In this research, we studied the roles of these four acidic residues in PARN thermal stability by mutational analysis. It was found that Mg2+ significantly decreased the rate but increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(70 reference statements)
1
7
0
1
Order By: Relevance
“…As temperature increased, all four proteins aggregated faster with an increase of the aggregation rate k and a decrease of the lag time t 0 . However, the maximum turbidity A lim reached its maximum at 53 • C. The k·A lim value, which reflects the initial velocity of the aggregation [33], has been suggested to be a better monitor than the single ones to evaluate the impact of mutations on aggregation [34]. Consistent with the exponential dependence of the Gibbs free energy changes on temperature, the log 10 (k·A lim ) value showed a linear dependence on temperature (Fig.…”
Section: The N-terminus Modulates the Thermal Aggregation Of Hcaf1supporting
confidence: 53%
“…As temperature increased, all four proteins aggregated faster with an increase of the aggregation rate k and a decrease of the lag time t 0 . However, the maximum turbidity A lim reached its maximum at 53 • C. The k·A lim value, which reflects the initial velocity of the aggregation [33], has been suggested to be a better monitor than the single ones to evaluate the impact of mutations on aggregation [34]. Consistent with the exponential dependence of the Gibbs free energy changes on temperature, the log 10 (k·A lim ) value showed a linear dependence on temperature (Fig.…”
Section: The N-terminus Modulates the Thermal Aggregation Of Hcaf1supporting
confidence: 53%
“…PARN follows a typical two‐metal‐ion catalytic mechanism, which may also adopt by the other deadenylases based on the high conservation of the active site in the catalytic domain. The existence of Mg 2+ in the active site of deadenylase is not only essential for its activity but also modulates its stability and/or interactions with the non‐nuclease domains . Besides Mg 2+ , the other divalent metal ions, such as Mn 2+ , Co 2+ , Ca 2+ , and Zn 2+ , may also be applicable for deadenylases and sometimes can modulate the substrate selectivity of the enzyme .…”
Section: Diversity Of Deadenylasesmentioning
confidence: 99%
“…Previous results have shown that the coordination of Mg 2+ stabilizes the active site of PARN, but promotes the aggregation of the 54 kDa PARN isoform at high temperatures [23], [36]. The effects of divalent metal ions on CrCaf1 stability was studied by thermal denaturation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the coordination of divalent metal ions in the active site might modulate the repulsion of the negative charges of the four acidic residues, which further stabilized the protein. It is worth noting that the turbidity, which reflects the size and amount of the aggregates, is not a good evaluator of the action of cosolutes in some cases [35], [36]. Thus a quantitative evaluation was achieved by measuring the aggregation kinetics at 55°C (Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation